Practicality and effectivity of figma-ctllm on poaceae diversity topic in developing critical thinking skills - Yudhistian; Cintamulya, Imas (Universitas Negeri Jakarta, 2024)
Creating creative, innovative, and effective learning to improve critical thinking skills along with the rapid development of ICT is a challenge for educators. Therefore, Figma CTL Learning Media (Figma-CTLLM) is a solution to the problem of answering the importance of developing learning media integrated with ICT while developing students' critical thinking skills. This study aims to describe the practicality of Figma-CTLLM on Poaceae diversity in developing critical thinking skills and to describe the effectiveness of Figma-CTLLM on the topic of Poaceae diversity seen from critical thinking skills and student responses. This type of research is Research and Development (R&D) research using the 4D model method (Define, Design, Develop and Disseminate). The research subjects consisted of 26 students. The research instruments were observation sheets to measure the implementation of Figma-CTLLM, CTS test questions sheets and questionnaires to determine student responses. The data analysis technique was quantitatively descriptive by calculating the percentage to describe the practicality and effectiveness of Figma-CTLLM implementation in developing CTS. The results of the analysis of the practicality test of Figma-CTLLM implementation in learning are in the category of very practical. The effectiveness test results were declared very effective by acquiring the average CTS measurement and the average student response assessment. Based on the study's results, the implementation of Figma-CTLLM in learning the diversity of Poaceae has met the criteria of practicality and effectiveness.